LBA8PROfound: Phase III study of olaparib versus enzalutamide or abiraterone for metastatic castration-resistant prostate cancer (mCRPC) with homologous recombination repair (HRR) gene alterations. (24th November 2019) - Sandhu, S K; Hussain, M; Mateo, J; Fizazi, K; Saad, F; Shore, N; Chi, K; Sartor, O; Agarwal, N; Olmos, D; Thiery-Vuillemin, A; Twardowski, P; et al.
Abstract: Background: Loss-of-function alterations in HRR genes are associated with response to PARP inhibition. PROfound (NCT02987543) is a randomized, open-label, Phase III trial evaluating efficacy and safety of olaparib (ola) vs enzalutamide (enza) or abiraterone (abi) in patients (pts) with mCRPC with alterations in any of 15 predefined genes with a direct or indirect role in HRR whose disease had progressed on prior new hormonal agent (NHA) therapy. Methods: Qualifying tumor tissue HRR alterations were centrally and prospectively identified using an investigational next-generation sequencing test (Foundation Medicine, Inc). Cohort A included pts with alterations in BRCA1, BRCA2 or ATM; Cohort B pts with any 1 of 12 other HRR alterations (BRIP1, BARD1, CDK12, CHEK1, CHEK2, FANCL, PALB2, PPP2R2A, RAD51B, RAD51C, RAD51D or RAD54L). Pts were randomized (2:1) to ola (300 mg bid) or physician's choice (pcNHA) of enza (160 mg/d) or abi (1000 mg/d + prednisone 5 mg bid). Primary endpoint was radiographic progression-free survival (rPFS) in Cohort A, assessed by blinded independent central review (BICR) and analyzed via stratified log-rank test. Crossover to ola was allowed after BICR progression. Results: 4425 men were screened; 245 randomized to Cohort A, 142 to Cohort B (65.6% had prior taxane). Efficacy is shown in the table. Most common adverse events (AEs) were anemia (46.5 v 15.4%), nausea (41.4 v 19.2%), decreased appetite (30.1 v 17.7%) and fatigue/asthenia (41.0 v 32.3%) for ola vs pcNHA; 18.0 and 8.5% of pts, respectively, discontinued due to AE. Conclusions: In pts with mCRPC and HRR alterations with prior NHA treatment, ola improved rPFS and ORR vs pcNHA, with a favorable trend for OS despite crossover. Safety was generally consistent with the known profile of ola. PROfound is the first positive Phase III biomarker-selected study evaluating a targeted treatment in pts with mCRPC. Clinical trial identification: NCT02987543. Editorial acknowledgement: Sarah Bulman, PhD, from Mudskipper Business Ltd, funded by AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Legal entity responsible for the study: AstraZeneca and Merck Sharp & Dohme Corp, a subsidiary of Merck & Co, Inc, Kenilworth, NJ, USA. Funding: AstraZeneca and Merck Sharp & Dohme Corp, a subsidiary of Merck & Co, Inc, Kenilworth, NJ, USA. Disclosure: M. Hussain: Honoraria (self), Lectures: Sanofi/Genzyme (women in Pca); Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Lectures: Genentech; Honoraria (self), Lectures: Research to Practice; Honoraria (self), Lectures: Aptitude Health; Honoraria (self), Lectures: Epics (covering 2019 GU ASCO; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer. J. Mateo: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy: Roche; Speaker Bureau / Expert testimony: Astellas; Speaker Bureau / Expert testimony: Sanofi. K. Fizazi: Honoraria (self), Advisory / Consultancy: Amgen; Honoraria (self), Advisory / Consultancy: Astellas; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: AAA; Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Advisory / Consultancy: Curevac; Honoraria (self), Advisory / Consultancy: Essa; Honoraria (self), Advisory / Consultancy: Janssen; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Orion; Honoraria (self), Advisory / Consultancy: Sanofi. F. Saad: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Janssen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Astellas. N. Shore: Advisory / Consultancy, Research grant / Funding (self): Amgen; Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy, Research grant / Funding (self): Bayer; Advisory / Consultancy, Research grant / Funding (self): BMS; Advisory / Consultancy, Research grant / Funding (self): Dendreon; Advisory / Consultancy, Research grant / Funding (self): Ferring; Advisory / Consultancy, Research grant / Funding (self): Janssen; Advisory / Consultancy, Research grant / Funding (self): Merck & Co.; Advisory / Consultancy, Research grant / Funding (self): MDx Health; Advisory / Consultancy, Research grant / Funding (self): Pfizer; Advisory / Consultancy, Research grant / Funding (self): Sanofi; Advisory / Consultancy, Research grant / Funding (self): Tolmar. K. Chi: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Astellas; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bayer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self), Research grant / Funding (institution): Sanofi; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca. O. Sartor: Advisory / Consultancy: Advanced Accelerator Applications, Astellas, AstraZeneca, Bayer, Blue Earth Diagnostics, Inc., Constellation, Dendreon, EMD Serono, Endocyte, Hinova, Johnson & Johnson, Myovant, Pfizer, Progenics, Sanofi; Research grant / Funding (institution): AstraZeneca, Bayer, Constellation, Dendreon, Endocyte, Innocrin, Invitae, Johnson & Johnson, Merck, Progenics, Roche, Sanofi, Sotio; Officer / Board of Directors, Co-chairman of GU Committee: NRG; Advisory / Consultancy, Consultant on Board of Scientific Counsellors: NCI; Speaker Bureau / Expert testimony: Sanofi; Non-remunerated activity/ies, Data safety monitoring: AstraZeneca, J&J, Pfizer, Myovant. N. Agarwal: Advisory / Consultancy: Astellas; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Argos; Advisory / Consultancy: BMS; Advisory / Consultancy: Bayer; Advisory / Consultancy: Clovis; Advisory / Consultancy: Eisai; Advisory / Consultancy: Exelixis; Advisory / Consultancy: EMD Serono; Advisory / Consultancy: Ely Lilly; Advisory / Consultancy: Foundation One; Advisory / Consultancy: Genentech; Advisory / Consultancy: Janssen; Advisory / Consultancy: Merck; Advisory / Consultancy: Medivation; Advisory / Consultancy: Novartis; Advisory / Consultancy: Nektar; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Pharmacyclics; Research grant / Funding (institution): AstraZeneca, Bavarian Nordic, BMS, Calithera, Celldex, Eisai, Exelixis, Genentech, GSK, Immunomedics, Janssen, Medivation, Merck, New link Genetics, Novartis, Pfizer, Prometheus, Rexahn, Sanofi Takeda, Tracon, Bayer, Clovis, EMD Serono, Ely Lilly, Janssen. D. Olmos: Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Astellas; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bayer; Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen; Speaker Bureau / Expert testimony: Sanofi-Aventis; Research grant / Funding (institution): Medivation/Pfizer; Research grant / Funding (institution): Tokai; Travel / Accommodation / Expenses: Ipsen; Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Genentech; Officer / Board of Directors, Directors Board Committee member: EORTC; Non-remunerated activity/ies: BioOncoTech & Tokai. A. Thiery-Vuillemin: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Sanofi; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Janssen; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Ipsen; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche/Genentech; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Honoraria (self), Advisory / Consultancy: Astellas Pharma. P. Twardowski: Speaker Bureau / Expert testimony: Sanofi; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bayer; Speaker Bureau / Expert testimony: Astellas; Speaker Bureau / Expert testimony: Pfizer; Speaker Bureau / Expert testimony: Janssen; Advisory / Consultancy: BMS. N. Mehra: Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy, Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Roche; Research grant / Funding (institution): Sanofi. C. Goessl: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. J. Kang: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. J. Burgents: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc.. W. Wu: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. A. Kohlmann: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. C. Adelman: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. J. de Bono: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Astellas; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Genentech/Roche; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Sanofi; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Merck Serono; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: GSK; Licensing / Royalties, X Rewards to Inventors with royalties paid to institution, no personal income, and a patent PARP inhibitors and DNA repair defects with royalties paid to institution, no personal income: Abiraterone; Travel / Accommodation / Expenses, Non-remunerated activity/ies: Genmab; Travel / Accommodation / Expenses, Non-remunerated activity/ies: Orion Pharma; Travel / Accommodation / Expenses, Non-remunerated activity/ies: Qiagen; Travel / Accommodation / Expenses, Non-remunerated activity/ies: Taiho Pharma; Travel / Accommodation / Expenses, Non-remunerated activity/ies: Vertex.